Correction: PCR-Free Enrichment of Mitochondrial DNA from Human Blood and Cell Lines for High Quality Next-Generation DNA Sequencing. - Meetha P Gould; Colleen M Bosworth; Sarah McMahon; Sneha Grandhi; Brian T Grimberg; Thomas LaFramboise (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0139253.].